Long-term risk of prostate cancer mortality among men with baseline prostate-specific antigen below 3 ng/ml: evidence from the finnish randomized study of screening for prostate cancer - Ola, Idris; Talala, Kirsi; Tammela, Teuvo; Taari, Kimmo; Murtola, Teemu J.; Kujala, Paula; Raitanen, Jani; Auvinen, Anssi (European urology oncology, 2025)
Background and objective - Despite the evidence for prostate-specific antigen (PSA) screening reducing prostate cancer (PCa) mortality, the optimal PSA cutoff and the clinical significance of low initial PSA levels in predicting long-term PCa mortality remain subjects of ongoing research. We assessed PCa mortality among men with initial PSA levels below 3 ng/ml during the first screening round of the Finnish Randomized Study of Screening for Prostate Cancer (FinRSPC). - Methods - A retrospective cohort study was conducted, including 20 268 men from the screening arm of the FinRSPC with an initial PSA level of <3 ng/ml, with follow-up spanning up to 20 yr. Hazard ratios (HRs) and their 95% corresponding confidence intervals (CIs) were estimated using a Cox regression analysis. - Key findings and limitations - During a median follow-up of 17.8 yr, 1840 PCa cases were diagnosed and 128 PCa deaths occurred, with the cumulative PCa mortality of 0.6% and a mortality rate of four per 10 000 person-years. PCa mortality was five-fold higher at PSA levels of 2-2.99 ng/ml (HR 5.0, 95% CI 3.1-8.1) than at <1 ng/ml. Deaths from cases with Gleason score <7 and European Association of Urology low-risk group tumors showed a stronger association with PSA, particularly in the 2-2.99 ng/ml range versus <1 ng/ml. Additionally, PCa mortality in younger men (55-58 yr at entry) exhibited a stronger association with PSA than that in older men (67-71 yr at baseline). Addition of the cumulative number of PSA tests slightly improved the overall prediction of PCa death based on Harrell’s C-statistic (base model 0.683 vs 0.717). The relatively small number of deaths, particularly among men with low-risk disease, may potentially limit the statistical precision of the results. - Conclusions and clinical implications - Our findings highlight the importance of a nuanced approach to PSA in PCa screening, suggesting utility for combining PSA with other tests at low levels and indicating minimal risk associated with discontinuing screening at ages 67-71 yr when PSA is low. - Patient summary - In this study, we analyzed prostate cancer deaths in Finnish men with low initial prostate-specific antigen (PSA) levels. We found that the risk of prostate cancer death increases in relation to PSA, especially in younger men. Screening might safely be stopped at ages 67-71 yr if PSA remains low.